2021
DOI: 10.1186/s41256-021-00192-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of preventive, supportive and awareness building measures among international students in China in response to COVID-19: a structural equation modeling approach

Abstract: Background Education institutions promptly implemented a set of steps to prevent the spread of COVID-19 among international Chinese students, such as restrictive physical exercise, mask wear, daily health reporting, etc. Success of such behavioral change campaigns largely depends on awareness building, satisfaction and trust on the authorities. The purpose of this current study is to assess the preventive, supportive and awareness-building steps taken during the COVID-19 pandemic for internatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…In addition, the intention of PA plays an essential role in predicting PA behavior (Cheon et al, 2012). Previous studies have applied the theory of planned behavior (TPB) to study an individual's intention and behavior (Sarker et al, 2021). Ajzen (1985) suggested TPB based on the theory of rational behavior (TRA), which believed that an individual's behavioral intention (INT) and behavior would be influenced by behavioral attitude (ATT), subjective norms (SNs), and perceived behavioral control (PBC; Ajzen, 1985;Venkatesh et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the intention of PA plays an essential role in predicting PA behavior (Cheon et al, 2012). Previous studies have applied the theory of planned behavior (TPB) to study an individual's intention and behavior (Sarker et al, 2021). Ajzen (1985) suggested TPB based on the theory of rational behavior (TRA), which believed that an individual's behavioral intention (INT) and behavior would be influenced by behavioral attitude (ATT), subjective norms (SNs), and perceived behavioral control (PBC; Ajzen, 1985;Venkatesh et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…An emerging number of studies has investigated the impact of the COVID-19 pandemic on higher education (see Ali, 2020;Patricia, 2020). However, being one of the most affected communities during the pandemic, international students were largely overlooked in literature (Sarker et al, 2021). The current study focused on international students who had been studying the Chinese language online since the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Since the worldwide spread of the COVID-19 pandemic, higher education has primarily converted online (Ali, 2020). The international student population was one of the most affected and vulnerable communities during the pandemic (Sarker et al, 2021). Research has reported challenges and difficulties faced by international students during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In the study, it was concluded that the pandemic awareness of elderly individuals, who were in the most important risk group during the COVID-19 pandemic, had significant effects on the perception of death anxiety and spiritual well-being and that the increase in pandemic awareness reduced death anxiety and increased spiritual well-being. It is of extreme importance to raise public awareness of the disease to decrease the rapid spread of COVID-19 and its adverse effects on health ( Sarker et al, 2021 ). Accordingly, it is believed that it is quite important for health personnel or health politicians to provide the necessary information about the pandemic to raise the awareness of elderly individuals about the disease.…”
Section: Discussionmentioning
confidence: 99%